Polytraps in European rural mountainous regions : an expert view - Sarkki, Simo; Lynn, Theo; Hiedanpää, Juha; Vizzarri, Matteo; Christoforidi, Irene; Brnkalakova, Stanislava; Crisan, Vlad; Egli, Antonia; Gultekin, Pinar; Gultekin, Yasar Selman; Jokinen, Mikko; Monteiro, Antonio T.; et al. (Taylor & Francis, 2025)
Many territorial and development policies in the European Union recognize that rural mountainous regions suffer from enduring natural and demographic disadvantages. These regions frequently face undesirable, persistent and self-reinforcing challenges, often conceptualized as traps. Through engagement with a panel of experts on mountainous regions, we examined whether the trap concept effectively explains the development challenges in European mountainous areas. We find that the distinguishing feature of these challenges is their multidimensional interrelatedness, which can give rise to multiple, simultaneously occurring traps (e.g. rigidity traps, poverty traps, lock-in traps, and regional development traps). In effect, we find that mountainous regions experience a polytrap – a complex of concurrent traps, maladaptive processes, an absence or severe limitation of bounce-back resilience, and difficulties in achieving bounce-forward resilience, largely due to dependence on external actors and factors. This polytrap concept emphasizes the need for rural policies to acknowledge these multifaceted challenges and both enable and promote place-based approaches for revitalizing left-behind places.
Keywords: marginalized areas; traps; Rural Development; resilience; polytraps